Light of devotion : oil lamps of Kerala - Bolon, Carol R., (Archaeopress Archaeology, 2022)
This in-depth study of the medieval oil lamps of Kerala and beyond considers these art objects as primary sources for a broader discussion on the ritual use of Hindu oil lamps, their related and unique cultural history, their motifs, style and subject matter. From an understudied region, many of the pieces presented are previously unpublished.